Outcomes After CT Angiography Versus Stress Testing in Diabetic Patients With Suspected Coronary Artery Disease - Sharma, Abhinav (J Am Coll Cardiol, 2019)
BACKGROUND: The optimal noninvasive test (NIT) for patients with diabetes and stable symptoms of coronary artery disease (CAD) is unknown. OBJECTIVE: To assess whether a diagnostic strategy based on coronary computed tomographic angiography (CTA) is superior to functional stress testing in reducing adverse cardiovascular (CV) outcomes (CV death or myocardial infarction [MI]) among symptomatic patients with diabetes. METHODS: The Prospective Multicenter Imaging Study for Evaluation of Chest Pain (PROMISE; NCT01174550) was a randomized trial evaluating an initial strategy of CTA versus functional testing in stable outpatients with symptoms suggestive of CAD. We compared CV outcomes in patients with diabetes (n=1,908 [21%]) and without diabetes (n=7,058 [79%]) based on their randomization to CTA or functional testing. RESULTS: Patients with diabetes (vs. without) were similar in age (median 61 vs. 60 years) and sex (female 54% vs. 52%) but had a greater burden of CV comorbidities. Patients with diabetes who underwent CTA had a lower risk of CV death/MI, compared to functional stress testing (CTA, 1.1% [10/936] vs. stress testing, 2.6% [25/972]; adjusted hazard ratio [aHR] 0.38, 95% CI 0.18–0.79; p=0.01). There was no significant difference in non-diabetics (CTA, 1.4% [50/3,564] vs. stress testing, 1.3% [45/3,494]; aHR 1.03, 95% CI 0.69–1.54, p=0.887; interaction term for diabetes p-value=0.02). CONCLUSIONS: In diabetics presenting with stable chest pain, a CTA strategy resulted in fewer adverse CV outcomes than a functional testing strategy. CTA may be considered as the initial diagnostic strategy in this subgroup.